Protection of Law and Justice and Human Rights must be Enforced Even in Large-Scale Social Restrictions - Youngky Fernando (Warmadewa Press, 2022)
Online media. TempoCOM. July 1, 2021. Restrictions on mobility in Java and Bali are getting more stringent. Online Law. July 4, 2021. The Advocate Profession Does Not Enter the Essential Sector, DetikNews. July 8, 2021. Metro Police Chief Promise. The Company Boss Brush Does Not Take Sides of Humanity. Supreme Court PR Announcement May 8, 2020. Circular Letter of the Secretary of the Supreme Court of the Republic of Indonesia Number 5 of 2020. Regarding Guidelines for the Implementation of Work From Home and the Imposition of Disciplinary Sentences for Judges and Apparatus within the Supreme Court of the Republic of Indonesia and the Judicial Bodies Under It During the Corona Virus Disease Community Emergency Period 2019. SINDOnews. October 24, 2020. Supreme Court. PERMA Number 4 of 2020. Date September 29, 2020, regarding the Administration and Trial of Criminal Cases in Courts Electronically. In the Indonesian Criminal Justice System: 1. Investigation: investigators together with an advocate accompanying the suspect; 2. Pre-prosecution: the public prosecutor and the judge and advocate were accompanying the defendant; 3. the judge's verdict: the judge together with the advocate accompanying the defendant; 4. After the criminal verdict: the prosecutor implements the final decision, and the advocate accompanies the defendant and officials from the state detention center or correctional institution. Detention in the Indonesian Criminal Justice System: 1. Investigation for a maximum of 60 days and or 120 days if the penalty is nine years or more; 2. The pre-prosecution is a maximum of 50 days and or 110 days if the punishment is nine years or more; 3. The pre-sentence is for a maximum of 90 days or 150 days if the sentence is nine years or more. Law Enforcers in the Indonesian Criminal Justice System: 1. Advocates as legal advisors or defenders of suspects and defendants and convicts requesting the judicial review; 2. Investigators; 3. Prosecutors; 4. Judge; 5. Officials of state land houses or correctional institutions. Instruction Letter from the Minister of Home Affairs Number 15 of 2021. On July 2, 2021, regarding the Implementation of Restrictions on Emergency Community Activities for Corona Virus Disease 2019. In the Java and Bali Regions. Cannot bind law enforcers in the Indonesian criminal justice system—Fiat Justitia Ruat Coelum (the justice law must be upheld even if the sky falls).